Pengaruh Mata Uang Digital Dalam Transformasi Pembayaran Elektronik - Anjani, Dela (BISMA : Business and Management Journal, 2023)
The aim of this research is to investigate the impact of digital currencies in changing the electronic payments ecosystem using a quantitative approach. In the ever-evolving digital era, digital currency has become a key element in the electronic payment process. This research uses quantitative data collected from transaction statistics and economic analysis to describe the changesthat occur. The research results show that digital currencies have significantly changed the way electronic payments are made. There has been a significant increase in the number of transactions involving digital currencies, and the use of digital currencies is becoming more pervasive in consumers' daily lives. Transaction efficiency and speed have increased, while transaction costs arerelatively lower. This research also reveals that digital currency adoption still depends on factors such as consumer knowledge, level of trust in technology, and perceived transaction security. Along with positive influences, this research also notes issues related to regulation of digital currencies that can affect the stability of the electronic paymentseco system. These results provide important insights for stakeholders in the electronic payments industry, as well as regulatory authorities who need to consider policies that support the development of digital currencies in the context of continuously evolving electronic payments.